Pattern of hematological malignancies diagnosed by peripheral smear examination - Paudyal, Punam; Pradhan, A; Pokharel, S; Shah, N; Pradhan, B; Poudel, P (Journal of BP Koirala Institute of Health Sciences, 2018)
Background: Leukemia is a malignant neoplasm of the hematopoietic stem cells. Examination of the peripheral blood smear is an inexpensive but powerful diagnostic tool in both children and adults suffering from leukemia because it provides rapid, reliable access to information about a variety of hematologic disorders.Objectives: To study the various patterns of leukemia, clinicoepidemiological profile and hematological features of leukemia.Materials and Methods: This is a cross sectional study conducted in the Hematology section of Department of Pathology of a tertiary care hospital. This study included all consecutive cases of leukemia diagnosed by peripheral blood smear examination from 1st June 2013 to 30th May 2014. The demographic indices were noted in a proforma. Investigations including haemoglobin estimation, total leucocyte count and platelet count were done for the study of hematological features. The morphological sub-typing was done according to the FAB classification system for leukemia.Results: Out of total 52 cases, majority of cases were of acute leukemia (65.38%), followed by chronic leukemia (26.92%) and lymphoma spill/ acute leukemia (7.69%). The age range was 2 to 90 years. Mean age was 37.6 year. Majority were male. Mean hemoglobin count for AML and ALL was 6.8 and 5.3 gm/dl respectively.Conclusion: The finding of this study reflects the pattern of leukemia at BPKIHS. Majority of acute leukemia constituted of acute myeloid leukemia (36.53%) cases and majority of chronic leukemia constituted of chronic myeloid leukemia (17.30%) cases.Journal of BP Koirala Institute of Health Sciences, Vol. 1, No. 1, 2018, Page: 25-35